2022
DOI: 10.1186/s12957-021-02479-w
|View full text |Cite
|
Sign up to set email alerts
|

High expression of PDZ-binding kinase is correlated with poor prognosis and immune infiltrates in hepatocellular carcinoma

Abstract: Background PDZ-binding kinase (PBK) encodes a serine/threonine protein kinase related to the dual specific mitogen-activated protein kinase kinase (MAPKK) family. There is evidence that overexpression of this gene is associated with tumorigenesis. However, the role of PBK in hepatocellular carcinoma (HCC) remains unclear. Therefore, we evaluated the prognostic role of PBK and its correlation with immune infiltrates in hepatocellular carcinoma. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Additionally, there might be some biases in the indication of preoperative supplemental treatment; this depends on the surgeons’ decision and the strategies of TAE followed by the radiologists. Furthermore, advanced HCC has various statuses to be discussed other than tumor size, such as lymph node metastasis [ 27 ], and clinical application of biomarker research to clarify the oncological characteristics of HCC is also a future issue [ 28 ]. Nevertheless, the results of this study are suggestive of the oncological effectiveness of the intended preoperative TAE for patients with a large HCC.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there might be some biases in the indication of preoperative supplemental treatment; this depends on the surgeons’ decision and the strategies of TAE followed by the radiologists. Furthermore, advanced HCC has various statuses to be discussed other than tumor size, such as lymph node metastasis [ 27 ], and clinical application of biomarker research to clarify the oncological characteristics of HCC is also a future issue [ 28 ]. Nevertheless, the results of this study are suggestive of the oncological effectiveness of the intended preoperative TAE for patients with a large HCC.…”
Section: Discussionmentioning
confidence: 99%
“…HCC comprises 75-85% of liver cancers and has a poor prognosis [1]. Some studies have shown multiple genes present good predictive potential in assessing HCC prognosis [15][16][17][18]. Recently, the importance of ICI therapy in HCC patients has been proven.…”
Section: Discussionmentioning
confidence: 99%
“…Generally speaking, a model with more genes and gene pairs will attain a higher AUC of OS. Second, our model did not include some earlier reported HCC prognosis genes [15][16][17][18]. Our prediction model only included 3 immune-related gene pairs with 6 genes to assess both the prognosis and treatment sensitivity to immune and targeted therapy of HCC patients, and it was hard to include all genes reported.…”
Section: Table 2 the Chi-square Test Of The Relation Between Risk Sco...mentioning
confidence: 99%
“…CMap ( https://clue.io/ ) [ 26 – 28 ] can be utilized to discover the mechanism of action of small molecules, functionally annotate genetic variants of disease genes, and inform clinical trials. The CMap database was updated with the top 50 EZH2-related up- and down-regulated genes from The Linked Omics database in order to predict potential drug targets for LUAD.…”
Section: Methodsmentioning
confidence: 99%